2020
DOI: 10.7341/20201625
|View full text |Cite
|
Sign up to set email alerts
|

How managerial coaching enables thriving at work. A sequential mediation

Abstract: The psychological state in which an individual experiences a form of vitality and a sense of learning at work is known as thriving at work. Since the new millennium, empirical research is evident that thriving (employees' sustainability) is critical for organizational sustainability. However, this human dimension of sustainability is understudied, and little is known about how individual characteristics and managers promote employee thriving at work. To address the gap, this pioneering study investigates the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Control variables. In order to determine the potential impact of other explanations on the empirical results, after a thorough review of the empirical studies on thriving at work, we chose age, gender and education level as control variables, which were also adopted by many scholars with thriving or stressors research (Li et al, 2019;Abid et al, 2020;Lin et al, 2020). Firstly, age is crucial to thriving, since elder people are more likely to be tired at work and unwilling to learn new knowledge (Kanfer and Ackerman, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Control variables. In order to determine the potential impact of other explanations on the empirical results, after a thorough review of the empirical studies on thriving at work, we chose age, gender and education level as control variables, which were also adopted by many scholars with thriving or stressors research (Li et al, 2019;Abid et al, 2020;Lin et al, 2020). Firstly, age is crucial to thriving, since elder people are more likely to be tired at work and unwilling to learn new knowledge (Kanfer and Ackerman, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Jex and Bliese (1999) found that self-efficacy is a mediator between time pressure, workload, task characteristics and physical and mental stress. In addition, Abid et al (2020) found that self-efficacy plays a mediating role between managerial coaching and thriving at work. We therefore suggest the following hypothesis: H5a: Challenge stressors promote thriving at work by enhancing self-efficacy.…”
Section: Mediating Effect Of Self-efficacymentioning
confidence: 99%
See 3 more Smart Citations